The price of truth : the journalist who defied military censors to report the fall of Nazi Germany - Fine, Richard (Cornell University Press, 2023)
"This book examines the circumstances of AP journalist Edward Kennedy's bypassing military censorship to break the news of the German surrender he had just witnessed on May 7, 1945, and assesses the controversy that followed"--